Marketing- and logistics-led organizations : creating and operating customer-focused supply networks - Mason, Robert; Evans, Barry, 1945- (Kogan Page, 2018)
"Logistics and marketing stand out as two disciplines which are connected, and both are critical to the provision of customer value. Marketing and Logistics Led Organizations looks at marketing-led logistics and logistics-led marketing. In the current business world, the idea of a single supply chain has been replaced by an integrated multi-channel approach. The authors therefore examine how to optimise profit and control costs through the coordination of these two functions. Marketing and Logistics Led Organizations takes an in-depth look at physical supply chains where manufacturing of a product occurs from groceries to pharmaceuticals, and from automotive to construction. The authors examine omni-channel, how this affects the customer experience and the need for a joined-up strategy which is operationalised across all channels. They also look at the challenges of digitalisation and the customer interface with the growth of the internet as well as the intensification of competition across all sectors"--Resumé vydavatele
"The Chartered Institute of Logistics and Transport"--Obálka
Keywords: logistika (management); marketing; business logistics; monografie; případové studie; monographs; case studies